Embedding Information Security into the Organization. - Johnson, M.E (IEEE Security and privacy : building confidence in a networked world)
Risk and business have always been inseparable, but new information security risks pose unknown challenges. How should firms organize and manage to improve enterprise security? Here, the authors describe how chief information security officer (CISOs) are working to build secure organizations.